2023
DOI: 10.1186/s12939-023-01875-w
|View full text |Cite
|
Sign up to set email alerts
|

The buffering effect of social capital for daily mental stress in an unequal society: a lesson from Seoul

Abstract: This study attempted to illustrate whether mental health deterioration could be alleviated by high social capital in an environment with high economic inequality. Daily mental stress was employed as a mental health factor when analyzing the association with economic inequality in the Seoul Survey data. Regarding social capital, community trust and altruism were included as cognitive dimensions, and participation and cooperation were included as structural dimensions in each model. The first finding showed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The manifestation of economic gaps is evident in various social gaps such as health and healthcare, culture and living, education and mindset, and physical gaps in residential and urban public spaces [24]. These gaps are linked to psychological health problems owing to the tendency to compare ourselves with others, increasing stress levels, and hindering social communication between groups [25][26][27].…”
Section: Relationship Between Discrimination Experience and Stress In...mentioning
confidence: 99%
“…The manifestation of economic gaps is evident in various social gaps such as health and healthcare, culture and living, education and mindset, and physical gaps in residential and urban public spaces [24]. These gaps are linked to psychological health problems owing to the tendency to compare ourselves with others, increasing stress levels, and hindering social communication between groups [25][26][27].…”
Section: Relationship Between Discrimination Experience and Stress In...mentioning
confidence: 99%
“…Previous research has for instance indicated that, in collectivistic countries, social approval has the same predictive power towards wellbeing as do individual emotions, whereas in Western high-income countries, social approval was shown to play a less important role than emotions [ 38 ]. Furthermore, the buffering effect of social capital (an interpersonal reserve) showed to be stronger in more unequal and collectivistic societies [ 39 ], and for people with a lower socio-economic position [ 40 , 41 ], compared with more equal societies and people with a higher socio-economic position, respectively. This additionally indicates that interpersonal reserves might play a larger explanatory role in health and wellbeing inequities among women working in FDI in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In collectivistic societies, the interconnectedness between people is more highly valued than individualistic societies [ 35 ]. Furthermore, in countries showing greater socio-economic inequalities and where more people experience financial scarcity (i.e., Ethiopia), the buffering effect of interpersonal reserves such as social capital might be greater than in countries that are more equal [ 39 ] and the value of money could be more pressing [ 42 44 ]. Therefore, we expect that, in the context of Ethiopia, interpersonal reserves and tangible reserves could play a more important role than intrapersonal reserves, considering the associations between SEP (independent variable) and mental health problems and wellbeing (dependent variables).…”
Section: Introductionmentioning
confidence: 99%